Validation of a rabbit model of irradiated bone healing: preliminary report - Desoutter Aline; Langonnet Stephan; Deneuve Sophie; Bera Jean-Christophe; Chaux-Bodar (EDP Sciences, 2020)
Introduction: External radiotherapy can lead to severe bone alteration. The aim of this pilot study was to validate a model for assessment of postextractional bone healing in the irradiated rabbit mandible. Material and method: The radiation protocol consisted of 5 sessions delivering 8.5 Gy each. Surgery was performed immediately after completion of radiotherapy. Sacrifices were performed from Day 0 to Day 42. Results: The bone mineral density and the trabecular number were decreased after radiotherapy whereas trabecular separation increased. The main differences between irradiated and non-irradiated rabbits were observed at Day 28 and 42. Discussion: Radiation seems to cause a delay in bone healing. It decreases bone quality and bone mineral density. Five sessions seem to be a valuable compromise between tissues effect and feasibility of the experiment. Conclusion: This model seems to be valuable for evaluating postextractional bone healing in the irradiated rabbit mandible.